The inducing power of Japanese technological innovation - Watanabe, Chihiro (Pinter Publishers, 1991)
The Japanese economy has achieved remarkable growth since the end of World War II, outpacing that of other advanced industrial nations. The most significant contribution to this growth has been the level of investment in technology. In contrast to other advanced economies, this investment has been funded primarily by private industry; the level of R & D investment by the Japanese government is the lowest among the advanced countries. There has been increasing interest in how the Japanese Government, especially MITI (Ministry of International Trade and Industry) is able to stimulate industrial research and development effectively by such limited financial means. This book tries to provide an answer to this question by analysing the inducing power of Japanese technological innovation.